Validation of Spectrophotometric Method to Quantify Veranicline Content in Tablets - Koçak, Engin; Çelebier , Mustafa; Altinöz, Sacide (Asian Journal of Chemistry, 2012)
Varenicline is a nicotinic receptor partial agonist used to treat smoking addiction. The objective of this work was to develope and validate UV-Vis spectrophotometric method for the determination of veranicline in tablets. In this study, 0.01 M phosphate buffer arranged to pH 7 was used to prepare standard stock solutions from varenicline tartrate salt, as well used to dissolve the commercials tablet and synthetic tablet solutions. UV-VIS spectrophotometric determination was performed at 319 nm wavelength having no interference coming from matrix components. The developed method was linear within the range 1-100 μg mL-1. Method validation was performed according to the ICH guideline and the results show that this simple and low cost method is precise, accurate, robust and rugged to be proposed for the routine analysis in quality control laboratories.